2003
DOI: 10.1099/ijs.0.02471-0
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium caminithermale sp. nov., a slightly halophilic and moderately thermophilic bacterium isolated from an Atlantic deep-sea hydrothermal chimney

Abstract: A strictly anaerobic, slightly halophilic and moderately thermophilic, sporulating rod designated strain DVird3 T was isolated from deep-sea hydrothermal vent samples collected at a depth of approximately 800 m on the Atlantic Ocean Ridge. Strain DVird3 T possessed a few laterally inserted flagella, had a DNA G+C content of 33?1 mol% and grew optimally at pH 6?6 and at 45˚C. Growth was observed at temperatures between 20 and 58˚C and at pH values between 5?8 and 8?2. The optimum NaCl concentration for growth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 35 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…C. caminithermale is strictly anaerobic and cannot use elemental sulfur, sulfate, thiosulfate, sulfite, nitrate or nitrite as electron acceptors (Brisbarre et al 2003).…”
Section: Bacterial Clone Library Analysismentioning
confidence: 99%
“…C. caminithermale is strictly anaerobic and cannot use elemental sulfur, sulfate, thiosulfate, sulfite, nitrate or nitrite as electron acceptors (Brisbarre et al 2003).…”
Section: Bacterial Clone Library Analysismentioning
confidence: 99%
“…DSM 2634=ATCC 13726). Subsequent analyses of 16S rRNA gene sequences showed that members of three proposed genera (listed as genera 6, 7 and 8 in Collins et al , 1994), namely ‘ C. aminobutyricum’ , Clostridium felsineum , Clostridium formicaceticum , and Clostridium halophilum , along with the more recently described Clostridium caminithermale , form a relatively compact separate group that also includes Clostridium aceticum and Anaerovirgula multivorans (Brisbarre et al , 2003; Chen et al , 2006; Pikuta et al , 2006; Gerritsen et al , 2014; Poehlein et al , 2015; Lawson et al , 2016). In the 2009 edition of Bergey’s, these species were assigned to Clostridiaceae 2, a sister group to Peptostreptococcaceae (Ludwig et al , 2009b), and are listed the same way in the SILVA database (Yilmaz et al , 2014).…”
mentioning
confidence: 99%
“…Relatively few studies have investigated mesophiles and moderate thermophiles among the heterotrophic anaerobic microbial groups thriving in deep-sea environments (Campbell et al, 2001;Brisbarre et al, 2003) compared with thermophiles and hyperthermophiles belonging to the Bacteria and Archaea (Baross & Deming, 1995;Jeanthon et al, 1998;L'Haridon et al, 1998;Reysenbach et al, 2000a, b;Wery et al, 2001;Alain et al, 2002a, b;Götz et al, 2002). Here we report on the isolation from a deep-sea hydrothermal vent on the 13 u N East Pacific Rise of a novel, moderately thermophilic, anaerobic, homolactic fermentative bacterium (strain 10C T ) belonging to the genus Exiguobacterium, order Bacillales, family Bacillaceae.…”
mentioning
confidence: 99%